Budlein A, a Sesquiterpene Lactone From Viguiera robusta, Alleviates Pain and Inflammation in a Model of Acute Gout Arthritis in Mice - Fattori, Victor; Zarpelon, Ana C.; Staurengo-Ferrari, Larissa; Borghi, Sergio M.; Zaninelli, Tiago H.; Da Costa, Fernando B.; Alves-Filho, Jose C.; Cunha, Thiago M.; Cunha, Fernando Q.; Casagrande, Rubia; Arakawa, Nilton S.; Verri, Waldiceu A. (Frontiers in Pharmacology, 2018)
Background: gout is the most common inflammatory arthritis worldwide. It is a painful inflammatory disease induced by the deposition of monosodium urate (MSU) crystals in the joints and peri-articular tissues. Sesquiterpene lactones (SLs) are secondary metabolite biosynthesized mainly by species from the family Asteraceae. It has been demonstrated that SLs present anti-inflammatory, analgesic, antitumoral, antiparasitic, and antimicrobial activities. In this study, we aimed at evaluating the efficacy of the SL budlein A in a model of acute gout arthritis in mice. Methods: experiments were conducted in male Swiss or male LysM-eGFP mice. Animals were treated with budlein A (1 or 10 mg/kg) or vehicle 30 min before stimulus with MSU (100µg/10µL, intra-articular). Knee joint withdrawal threshold and edema were evaluated using electronic von Frey and caliper, respectively, 1-15h after MSU injection. Leukocyte recruitment was determined by counting cells (Neubauer chamber), H&E staining, and using LysM-eGFP mice by confocal microscopy. Inflammasome components, Il-1β, and Tnf-α mRNA expression were determined by RT-qPCR. IL-1β and TNF-α production (in vitro) and NF-κB activation (in vitro and in vivo) were evaluated by ELISA. In vitro analysis using LPS-primed bone marrow-derived macrophages (BMDMs) was performed 5h after stimulation with MSU crystals. For these experiments, BMDMs were either treated or pre-treated with budlein A at concentrations of 1, 3, or 10μg/mL. Results: we demonstrated that budlein A reduced mechanical hypersensitivity and knee joint edema. Moreover, it reduced neutrophil recruitment, phagocytosis of MSU crystals by neutrophils, and Il-1β and Tnf-α mRNA expression in the knee joint. In vitro, budlein A decreased TNF-α production, which might be related to the inhibition of NF-κB activation. Furthermore, budlein A also reduced the IL-1β maturation, possibly by targeting inflammasome assembly in macrophages. Conclusion: budlein A reduced pain and inflammation in a model of acute gout arthritis in mice. Therefore, it is likely that molecules with the ability of targeting NF-κB activation and inflammasome assembly, such as budlein A, are interesting approaches to treat gout flares.